Four-dimensional XStrain echocardiography: Correlation of aortic stiffness with left ventricular diastolic, systolic, and strain parameters in healthy adults – A single-center Indian perspective - Akhil Mehrotra; Ajay Sharma; Mohammad Shadab; Om Prakash; Shubham Kacker (Journal of Indian College of Cardiology, 2023)
Background: Interrelationship of arterial stiffness with diastolic impairments of left ventricle (LV) in healthy population has been reported in several studies; however, to the best of our knowledge, no study till date has evaluated the relationship of aortic stiffness, with LV diastolic, systolic, and strain components, in healthy adults, by conventional, tissue Doppler imaging, and speckle-tracking echocardiography. Materials and Methods: Fifty-eight healthy participants were recruited (38 males and 20 females), and their mean age was 30.53 ± 12.22 years and 35.25 ± 10.61 years, respectively. A detailed assessment of aortic stiffness and elasticity, LV systolic, diastolic, and strain parameters was performed by the ingenious technology of four-dimensional XStrain echocardiography. Moreover, Pearson's correlation coefficient was employed to investigate the association of aortic stiffness with LV diastolic, systolic, and strain functions. Results: A significant relationship was documented between aortic stiffness and a number of parameters of LV diastolic and systolic functions. On the contrary, there was an insignificant trend of positive or negative correlation of aortic stiffness with LV strain. Conclusion: This is the first study to document the correlation between aortic stiffness and various LV functions in healthy adults.